The Influence of Children Song on Memorizing Vocabulary to Young Learner as Foreign Language of Fifth Grade of SDN Tanjung I Pademawu Pamekasan - Akhmad Zainol Fatahillah; Muhammad Darrin Zuhri (The Ellite of Unira, 2019)
The objectives of this research are to know whether English song can improve the students’ vocabulary at fifth Grade of SDN Tanjung I Pademawu. The result of the data analysis proved that the value of t-test (tobs is 8,742 and ttable is 2,021). It means that tobs is higher than ttable(8,742>2,021). Based on the criteria for testing hypothesis was if the value of t obtained is higher than t table at significant level 0,05 the null hypothesis (Ho) is rejected and hypothesis alternative (HI) is accepted. The researcher came to conclusion that “there was significant Influence of English Song Toward Students’ Vocabulary Mastery and students’ motivation at the fifth Grade of SDN Tanjung I Pademawu.